A feasibility study of microwave ablation for papillary thyroid cancer close to the thyroid capsule. (1st January 2021) - Wu, Jie; Zhao, Zhen-Long; Cao, Xiao-Jing; Wei, Ying; Peng, Li-Li; Li, Yan; Yu, Ming-An
Abstract: Background: To evaluate the feasibility, efficiency, and safety of microwave ablation (MWA) for papillary thyroid carcinoma (PTC) close to the thyroid capsule. Methods: The data of 106 cases who underwent thermal ablation from June 2014 to September 2020 were retrospectively analyzed. The mean follow-up time was 25 ± 11 months (range, 9–48 months). The strategy of fluid isolation was successfully applied in all cases, and all PTC nodules underwent extended ablation. The technical feasibility, technical success rate, and safety were analyzed. Changes in tumor size at different time points after MWA were evaluated. Results: According to the contrast-enhanced ultrasound results after ablation, MWA has been successfully applied in all enrolled cases. The capsular ablation has also been achieved for all cases. Nodules in 71 cases (70.0%) completely disappeared in the follow-up period. No local recurrence was detected. The incidence of lymph node metastasis and new tumors was 1.9% (2/106) respectively. Light voice changes were the only complication, with a rate of 5.7% (6/106), which were relieved within 6 months after MWA. The size of the ablation zone increased firstly in 6 months after MWA compared with the pretreatment tumor size ( p  < 0.05). At 12, 18, 24, 30, 36 and 42 months after MWA, the ablation zone shrank and the sizes were smaller than the tumor size before MWA ( p  < 0.05 for all). Conclusions: MWA is an effective, safe, and feasible method in treating PTC close to the thyroid capsule.